The Effect of Workload, Dual Role Conflict Working Hours, and Job Stress on The Performance of Female Nurse at Stella Maris Hospital In 2024 - Zubaidah P.D Barang,; Atjo Wahyu,; Lalu Muhammad Saleh,; M. Furqaan Naiem,; Masyita Muis,; Wahiduddin,; Anwar Mallongi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: In an increasingly competitive work environment, the dual roles assumed by female nurses present significant challenges, particularly in balancing work and family demands. This study aims to analyze the influence of work-family conflict, workload, and working hours on the performance of female nurses at Stella Maris Hospital, with work stress serving as a mediating variable. Methods: This research employs a quantitative approach using a survey method. The sample value (n) obtained was 91 people. The variable in this research is workload, dual role conflict working hours and stress of performance. Data were collected through questionnaires completed by female nurses at the hospital and analyzed using path analysis to identify both direct and indirect effects among the variables studied. Results: The study found that work-family conflict has a significant direct impact on the decline in female nurses' performance (p = 0.007), while workload (p = 0.508) and working hours (p = 0.174) do not have a significant direct influence. Work stress, measured both subjectively (through questionnaires) and objectively (using a colorimeter) (t-value < t-table), was not found to significantly mediate the relationship between work-family conflict, workload, working hours, and nurse performance. Conclusion: Work stress triggered by excessive workload, dual role conflict, and irregular working hours plays a critical role in reducing the performance of female nurses. Therefore, better management strategies are needed to minimize the negative impacts of these factors to achieve optimal performance.